A portable cosmos revealing the Antikythera mechanism, scientific wonder of the ancient world - Jones, Alexander 1960- (Oxford University Press, 2017)
"The Antikythera Mechanism, now 82 small fragments of corroded bronze, was an ancient Greek machine simulating the cosmos as the Greeks understood it. Reflecting the most recent researches, A Portable Cosmos presents it as a gateway to Greek astronomy and technology and their place in Greco-Roman society and thought"...
Keywords: Mechanismus von Antikythera; HISTORY / Ancient / Greece; Funde; Geschichte; Naturwissenschaft; Antikythera mechanism (Ancient calculator); Astronomy, Ancient -- Greece; Calendar, Greek; Science -- Greece -- History -- To 1500; Technology -- Greece -- History -- To 1500; Griechenland; Greece -- Intellectual life -- To 146 B.C.; Greece -- Antiquities; Antikythēra Island (Greece) -- Antiquities